Peto’s Paradox: Evolution’s Prescription for Cancer Prevention - Caulin, Aleah F. (2011)
The evolution of multicellularity required the suppression of cancer. If every cell has some chance of becoming cancerous, large, long-lived organisms should have an increased risk of developing cancer compared to small, short-lived organisms. The lack of correlation between body size and cancer risk is known as Peto’s Paradox. Animals with 1,000 times more cells than humans do not exhibit an increased cancer risk, suggesting that natural mechanisms can suppress cancer 1,000 times more effectively than is done in human cells. Because cancer has proven difficult to cure, attention has turned to cancer prevention. In this review, like pharmaceutical companies mining natural products, we seek to understand how evolution has suppressed cancer to ultimately develop improved cancer prevention in humans.